(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Essential oils are having wide range of biological activity is used to achieve therapeutic effects. These are volatile substances sensitive to oxygen, light, moisture and heat. In the present study microemulsion formulation was prepared using a blend of essential oil contains cardamom, coriander, fennel, caraway, ajowan and peppermint oil, water and non ionic surfactant tween 20 and cosurfactant as ethanol. Each essential oil was extracted from dried seed by steam distillation and characterized by Headspace Gas chromatography use of a marker compound which was linalool for coriander oil, cineol for cardamom oil, anethol for fennel oil, carvone for caraway oil, thymol for ajowan oil and menthol for peppermint oil. The marker compound was characterized using mass spectroscopy. Microemulsion of oil showed higher stability with droplet size in the range of 110-410nm. The product then screened for in vitro antacid properties which showed significant positive response.